MODEL PEMBELAJARAN GREEN CONSTITUTION DALAM MENGEMBANGKAN CIVIC ENGAGEMENT PESERTA DIDIK PADA PROGRAM ADIWIYATA (Studi di SMAN 12, SMKN 5 dan SMKN 7 BANDUNG) - Fanny Dwi Octaviany, - (2020)
Environmental damage must be considered from a small scope but has a large impact, environmental damage but internationally many of them also damage the environment consciously or not, so that it is not only the responsibility of the state but every country must be able to protect the environment. This research was conducted so that government programs, especially in schools, could be thoroughly integrated. Due to the lack of student participation, therefore through the Green Constitution to develop student Civic Engagement, it is hoped that the character of students will be ready to become responsible citizens. The method used by researchers is qualitative, by gathering information through observation, interviews and documentation studies. After the research was carried out, this model was successful despite experiencing differences in outcomes for each school. Keywords: Green Constitution, Civic Engagement, Students, Adiwiyata